2010
DOI: 10.7196/samj.4098
|View full text |Cite
|
Sign up to set email alerts
|

Vuvuzela sound measurements

Abstract: 1 reported the maximum output levels of a vuvuzela at various distances from the horn. In response to enquiries, we provide additional information on the method and results reported in the earlier paper.One commercial vuvuzela was used in the recording of sound levels at 4 different positions: (i) at the ear of the person blowing the vuvuzela; (ii) at the bell end; (iii) 1 m from the bell end; and (iv) 2 m from the bell end. All measurements were made approximately 1.6 m from the ground, in an openair setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A further improvement in this technique has been suggested by CSRIO (9). Since milling acid dyes show little migration during boiling, there is no need to use a prolonged heat treatment once a level strike has been achieved.…”
Section: Figure 2-rate Of Exhaustion Of a Blue Phthalocyanine Millingmentioning
confidence: 99%
“…A further improvement in this technique has been suggested by CSRIO (9). Since milling acid dyes show little migration during boiling, there is no need to use a prolonged heat treatment once a level strike has been achieved.…”
Section: Figure 2-rate Of Exhaustion Of a Blue Phthalocyanine Millingmentioning
confidence: 99%
“…They have been banned from a number of sports grounds due to the volume of noise emitted and safety concerns arising from their ability to nullify public address systems. Studies have previously suggested that vuvuzela playing poses a risk of noise induced hearing loss [37] , [38] . We recommend that consideration is taken of their propensity to disseminate respiratory aerosols and that persons with respiratory infections be advised not to blow their vuvuzela in places where they risk infecting others.…”
Section: Discussionmentioning
confidence: 99%
“…n 0 ) 3 (n ? n s 2 ), C = 2(n 2 -n 0 ) (n 2 -n s 2 ), D = (n -n 0 ) 3 (n -n s 2 ), u = 4pnd/k and x is the absorbance that is given by x = exp(-ad).The idea of creating envelopes in the interference zone, proposed by Manifacier et al [25], has been developed by Swanepoel [18,19] to determine the thickness of a homogeneous thin film form the Ch-Gs materials (Inset of Fig. 1 shows the envelopes of the interference maxima and minima).…”
Section: Determination Of the Film Thicknessmentioning
confidence: 97%
“…The thickness of the (As 2 S 3 ) 0.95 Cu 0.05 film was calculated based on the envelopes of the transmission spectrum using the Swanepoel Theory [18,19]. The envelope technique enabled the determination of the average thickness and the refractive index of the Ch-Gs films with accuracy better than 1% [20].…”
Section: Determination Of the Film Thicknessmentioning
confidence: 99%